Analisis Resepsi Mahasiswa Ilmu Komunikasi Unud Terhadap Tayangan ASMR ‘Eat with Boki’ - Diah Utami Dewi, I Gusti Ayu Agung; Purnawan, Ni Luh Ramaswati; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium; Vol 2 No 2 (2021): Jurnal Ilmu Komunikasi Vol 2 No 2 Tahun 2021, 2021)
The trend of ASMR mukbang videos in Indonesia has increased since March 2018. ASMR mukbang videos are widely broadcast by Korean Youtubers, one of which is the 'Eat with Boki' ??account. It is proven that as of October 2020 the 'Eat with Boki' ??account has reached 4.65 million subscribers. The video content of 'Eat with Boki' ??is ASMR mukbang did by Moon Bokhee. This study aims to determine the reception that occurred to Communication Science students at Udayana University after watching the ASMR mukbang video ‘Eat with Boki’. The theory used in this study is Stuart Hall's Reception Theory with the analysis of Stuart Hall's Reception Analysis. The type of research used is descriptive-qualitative. This study involved six informants. The results of the analysis in this study that four people into the Dominant Position category, one person into the Negotiated Position category and one person into the Oppositional Position category. Keyword s: Reception, ASMR, Eat with Boki, Youtube